2013
DOI: 10.1039/c3sm50945a
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced phase transitions of colloidal monolayers with crystalline order

Abstract: We experimentally study the phase behavior of a charge-stabilized two-dimensional colloidal crystal which is subjected to a one-dimensional periodic light field. Such light fields are created by a scanned optical line tweezer which allows the variation of the periodicity without optical realignments. In order to realize a wide range of line spacings relative to the lattice constant, we use a suspension of silica particles in bromobenzene. This colloidal system has a Debye screening length of about 4.6 mm which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Model systems composed of colloidal particles in periodic potentials have been studied for a number of years [28,29], from simple double well potentials [30][31][32][33] to directed motion [34][35][36][37][38][39], particle sorting [40], and kink generation [41] in two-dimensional (2D) optical lattices. Colloidal systems are easy to manipulate, and have accessible length and time scales, making them attractive models for the study of synchronisation at the microscale.…”
Section: Introductionmentioning
confidence: 99%
“…Model systems composed of colloidal particles in periodic potentials have been studied for a number of years [28,29], from simple double well potentials [30][31][32][33] to directed motion [34][35][36][37][38][39], particle sorting [40], and kink generation [41] in two-dimensional (2D) optical lattices. Colloidal systems are easy to manipulate, and have accessible length and time scales, making them attractive models for the study of synchronisation at the microscale.…”
Section: Introductionmentioning
confidence: 99%
“…Under micro-gravity conditions hard sphere crystal nucleation and growth was templated on seed crystals placed in the bulk of the host suspension [22]. In addition to topological templates exploiting excluded volume interactions, also light grids exploiting photophoresis were used to fabricate individual 2D crystals and quasi-crystals [23,24]. Use of holographic tweezer trapped seed structures allowed precise localization and orientation in 3D [25].…”
Section: Introductionmentioning
confidence: 99%
“…The potential maxima are indicated by the darker shadings, so the vortices are attracted to the light colored regions. This type of system has been studied previously for colloids interacting with q1D periodic substrate arrays, where it was shown that various melting and structural transitions between hexagonal, smectic, and disordered colloidal arrangements can occur [46][47][48][49][50][51][52] . In general, the colloidal studies focused on the case where the particle lattice constant a is larger than the substrate lattice constant w. Martinoli et al investigated vortex pinning in samples with a 1D periodic thickness modulation [53][54][55] and observed broad commensuration peaks in the depinning threshold that were argued to be correlated with the formation of ordered vortex arrangements that could align with the substrate periodicity.…”
Section: Introductionmentioning
confidence: 99%